2018
DOI: 10.1097/md.0000000000012264
|View full text |Cite|
|
Sign up to set email alerts
|

Efficacy of light-emitting diode (LED) photobiomodulation in pain management, facial edema, trismus, and quality of life after extraction of retained lower third molars

Abstract: Background:In dentistry, one of the most common surgical procedures is the removal of retained third molars. This surgery generates great morbidity to the participants for causing pain, edema, and trismus due to surgical trauma. The objective of the present study is to evaluate the efficacy of photobiomodulation with light emitting diode (LED) in the control of pain, facial edema, trismus, and quality of life resulting from the extraction of retained lower third molars.Methods:A randomized, double-blind, place… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0
5

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 17 publications
0
4
0
5
Order By: Relevance
“…Esses aparelhos são nomeados de acordo com as substâncias radioativas que eles contêm e essas substâncias podem estar na forma de cristais sólidos, ou na forma de semicondutores diodos que também são classificados pela potência, dividindo-se em laser de alta potência ou de baixa potência (Convissar, et al, 2019;Zerbinati, et al, 2014). Sua eficácia depende dos parâmetros, como o comprimento de onda, potência e energia e diferentes situações clínicas na odontologia requerem diferentes protocolos de LBI (Tenis, et al, 2018). Pedreira e Medrado, et al, (2013) Acrescenta, que o laser é capaz de gerar um feixe de luz monocromático quando provocado por uma fonte de energia.…”
Section: Resultsunclassified
“…Esses aparelhos são nomeados de acordo com as substâncias radioativas que eles contêm e essas substâncias podem estar na forma de cristais sólidos, ou na forma de semicondutores diodos que também são classificados pela potência, dividindo-se em laser de alta potência ou de baixa potência (Convissar, et al, 2019;Zerbinati, et al, 2014). Sua eficácia depende dos parâmetros, como o comprimento de onda, potência e energia e diferentes situações clínicas na odontologia requerem diferentes protocolos de LBI (Tenis, et al, 2018). Pedreira e Medrado, et al, (2013) Acrescenta, que o laser é capaz de gerar um feixe de luz monocromático quando provocado por uma fonte de energia.…”
Section: Resultsunclassified
“…15 Clinical studies have also provided promising results of LED therapy. 17,18,28 Corti et al evaluated 12 patients who were affected by hematological tumors and developed OM after high-doses of chemotherapy and were treated with LED. The study showed that LED treatment was safe and capable of reducing the duration of oral lesions.…”
Section: Discussionmentioning
confidence: 99%
“…Além disso, o laser de baixa potência tem sido de grande valia em casos de aftas, tratamento de afecções orofaciais, alveolite, disfunções da ATM, sensibilidade pós restaurações, úlceras, queilite, lesões herpéticas, inflamações de mucosa, remodelação óssea, osteorradionecrose e xerostomia (SANTOS et al,2021). Considerando que a eficácia depende dos parâmetros: comprimento de onda, potência e energia, visto que em diferentes situações clínicas odontológicas requerem diferentes protocolos (TENIS et al, 2018).…”
Section: Revisão De Literaturaunclassified